Hemodynamic profile, responsiveness to anandamide, and baroreflex sensitivity of mice lacking fatty acid amide hydrolase - Pacher, Pál (2005)
The endocannabinoid anandamide exerts neurobehavioral, cardiovascular, and immune-regulatory effects through cannabinoid receptors (CB). Fatty acid amide hydrolase (FAAH) is an enzyme responsible for the in vivo degradation of anandamide. Recent experimental studies have suggested that targeting the endocannabinergic system by FAAH inhibitors is a promising novel approach for the treatment of anxiety, inflammation, and hypertension. In this study, we compared the cardiac performance of FAAH knockout (FAAH(−/−)) mice and their wild-type (FAAH(+/+)) littermates and analyzed the hemodynamic effects of anandamide using the Millar pressure-volume conductance catheter system. Baseline cardiovascular parameters, systolic and diastolic function at different preloads, and baroreflex sensitivity were similar in FAAH(−/−) and FAAH(+/+) mice. FAAH(−/−) mice displayed increased sensitivity to anandamide-induced, CB(1)-mediated hypotension and decreased cardiac contractility compared with FAAH(+/+) littermates. In contrast, the hypotensive potency of synthetic CB(1) agonist HU-210 and the level of expression of myocardial CB(1) were similar in the two strains. The myocardial levels of anandamide and oleoylethanolamide, but not 2-arachidonylglycerol, were increased in FAAH(−/−) mice compared with FAAH(+/+) mice. These results indicate that mice lacking FAAH have a normal hemodynamic profile, and their increased responsiveness to anandamide-induced hypotension and cardiodepression is due to the decreased degradation of anandamide rather than an increase in target organ sensitivity to CB(1) agonists.